Tratamento de água produzida com novos sistemas microemulsionado: avaliação da qualidade e aplicação na germinação de sementes de girassol - Oliveira, Gregory Vinicius Bezerra de (2019)
Produced water (PW) is the main effluent formed due to extraction of petroleum and is characterized by a large amount of contaminants, requiring the application of treatment processes to reduce the amount of these pollutants. Reuse of treated water is important in combating the scarcity of water resources, especially in the agricultural sector, the main water consumer in the world. With this, the current work aimed to evaluate the removal of metals Ba+ , Ca2+, Cr3+, Fe3+, Li+ , K+ , Mg2+, Mn2+, Na+ , Sr2+ from the PW using a microemulsion system consisting of biodegradable componentes and to evaluate the effects of treated produced water (TPW) on the sunflower seeds germination. Two sytems were used for the study, containg in its compositions Tween 20 as surfactant (S), Ethyl Acetate as organic phase (PO), Produced Water (PW) and Water Supply (WS) as aqueous phase (PA). For the system using PW, seven points were chosen within the Winsor II region, in which case the excess aqueous phase was collected for analysis. The optimum removal point was P3 (25% S, 20% PO, 55% PA), obtaining a removal of more than 50% for most metals. For the system where WS is the PA, three points were chosen within the region of Winsor II where the microemulsion of these were collected and mixed with the PW in volumetric ratios of application 1, 2 and 3 of PW/Microemulsion. The removal of greater was found when using the microemulsion of point C (20% S, 50% PO, 30% PA) with the application ratio of 2 (PW/Microemulsion), obtaining a removal of more than 60% for most metals.The greatest removal of metals was found when the microemulsion of the C point (20% T, 50% FO, 30% FA) was used with the application ratio 2, obtaining a removal of more than 60% for most metals, this was the selected point for for evaluation in germination of sunflower. For most of the metals, concentrations found on TPW fits within the ideal parameters for use in irrigation. In the application for sunflower germination the TPW and its dilutions had satisfactory results for all germination parameters studied, presenting performance similar to supply water. It was possible to verify that the microemulsion system used was efficient, with irrigation being an alternative for the reuse of the treated produced water.